Removal of N-nitrosodimethylamine precursors with powdered activated carbon adsorption - Beita Sandí, Wilson (2016)
The main objective of this study was to examine the roles of powdered activated carbon (PAC) characteristics (i.e., surface chemistry, pore size distribution, and surface area) in the removal of N-nitrosodimethylamine (NDMA) formation potential (FP) in surface and wastewater-impacted waters. Also, the effects of natural attenuation of NDMA precursors in surface waters, NDMA FP concentration, and carbon dose on the removal of NDMA FP by PAC were evaluated. Finally, the removal of NDMA FP by PAC at two full-scale DWTPs was monitored. Wastewater-impacted and surface water samples were collected to conduct adsorption experiments using different PACs and activated carbon fibers (ACFs) with a wide range of physicochemical characteristics. The removal efficiency of NDMA FP by PAC was significantly higher in wastewater-impacted than surface waters. Adsorbable NDMA precursors showed a size distribution in the waters tested; the adsorbable fraction included precursors accessing the pore size regions of 10–20 Å and <10 Å. Basic carbons showed higher removal of NDMA FP than acidic carbons on a surface area basis. The overall removal of NDMA FP by PAC on a mass basis depended on the surface area, pore size distribution and pHPZC. Thus, PACs with hybrid characteristics (micro and mesoporous), higher surface areas, and basic surface chemistry are more likely to be effective for NDMA precursor control by PAC adsorption. The application of PAC in DWTPs for taste and odor control resulted in an additional 20% removal of NDMA FP for the PAC doses of 7–10 mg/L. The natural attenuation of NDMA precursors through a combination of processes (biodegradation, photolysis and adsorption) decreased their adsorbability and removal by PAC adsorption.